Safety and pharmacokinetics of MM-302, a HER2-targeted antibody–liposomal doxorubicin conjugate, in patients with advanced HER2-positive breast cancer: a phase 1 dose-escalation study. Issue 9 (30th October 2018) - Munster, Pamela; Krop, Ian; LoRusso, Patricia; Ma, Cynthia; Siegel, Barry; Shields, Anthony; Molnár, István; Wickham, Thomas; Reynolds, Joseph; Campbell, Karen; Hendriks, Bart; Adiwijaya, Bambang; et al.
Abstract Background This phase 1 dose-escalation trial studied MM-302, a novel HER2-targeted PEGylated antibody–liposomal doxorubicin conjugate, in HER2-positive locally advanced/metastatic breast cancer. Methods Patients were enrolled in four cohorts: MM-302 monotherapy (8, 16, 30, 40, and 50 mg/m2 every 4 weeks [q4w]); MM-302 (30 or 40 mg/m2 q4w) plus trastuzumab (4 mg/kg q2w); MM-302 (30 mg/m2 ) plus trastuzumab (6 mg/kg) q3w; MM-302 (30 mg/m2 ) plus trastuzumab (6 mg/kg) and cyclophosphamide (450 mg/m2 ) q3w. Results Sixty-nine patients were treated. The most common adverse events (AEs) were fatigue and nausea. Grade 3/4 AEs of special interest included neutropenia, fatigue, mucosal inflammation, anemia, thrombocytopenia, febrile neutropenia, and palmar-plantar erythrodysesthesia. The MTD was not reached. With MM-302 ≥ 30 mg/m2, overall response rate (ORR) was 13% and median progression-free survival (mPFS) 7.4 months (95% CI: 3·5–10·9) in all arms. In 25 anthracycline-naïve patients, ORR was 28·0% and mPFS 10·9 months (95% CI: 1·8–15·3). Imaging with64 Cu-labeled MM-302 visualized tumor-drug penetrance in tumors throughout the body, including the brain. Conclusion MM-302 monotherapy, in combination with trastuzumab, or trastuzumab plus cyclophosphamide, was well tolerated and showed promising efficacy. The selected phase 2 MM-302 dose was 30 mg/m2 plus 6 mg/kg trastuzumab q3w.